Alkemičarka gline svjetskoga glasa - Stančić, Stanko (Array, 2008)
Eminent Croatian and international ceramicist Seka Severin Tudja (1923 – 2007) created an idiosyncratic world of shapes of unsurpassed sculptural and pictorial value, working in exile in Caracas a full 55 years. Some of Seka's representative works can be seen in her native Zagreb, works she granted to the Arts & Crafts Museum after a grand retrospective exhibition staged in 1998. As a prominent figure of the art scene she represented Venezuela for forty-three years at the World Crafts Council. Seka was a member of the Geneva-based Academie International de la Ceramique from 1972 and was from 1979 an honorary member of the Asociacion Venezolana de las Artes del Fuego in Caracas. She studied sculpting from 1942 to 1945 at the Visual Arts Academy in Zagreb in the classes of Professors Frano Kršinić and Krsto Hegedušić. In 1946 she departs for Paris with a scholarship from the French government to study sculpting and drawing at the La grande Chaumière academy where she also completes her studies of art history and archaeology at Paris' Sorbonne. In Paris she had her first contact with ceramics; making clay figures for an animated film, collaborating with pottery workshops and for her own amusement begins modelling her own small potteries. She moves to Caracas, Venezuela, in 1952 where she launched her true ceramic creativity. Seka demonstrated supreme skill in shaping ceramics. But she was always something more than just a master of her craft. Seka was an alchemist that created objects out of clay and glaze that took on the characteristics of tin, bronze and gold.